Penerapan Produksi Bersih pada Kelompok Tani Tunas Muda Di Desa Pudak Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Jalius Jalius; Fachroerozi Hoesni; Firmansyah Firmansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of the study was to find out the Tunas Muda farmer group applied clean production. The object of research is a member of the Tunas Muda farmer group who raises beef cattle in Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency. The research method is a survey, census data collection, interviews, and direct observation. Secondary data were obtained from the Pudak village head office, the Kumpeh Ulu sub-district office, and the Muaro Jambi Livestock Service. The results showed that the Tunas Muda farmer group in Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency had utilized livestock waste (clean production), including 0.5% biogas waste and 100% of the waste was used as organic fertilizer. Of the 20 members, only 1 member (5%) processes livestock manure into biogas and organic fertilizer. The average production of fresh peces is 842 kg per day and the average production of organic fertilizer is 587.9 kg per day. The conclusion is that the Tunas Muda farmer group has not optimally applied clean production, namely the manufacture of biogas and organic fertilizer. The advantage of reducing environmental pollution, can increase income and make it easier for farmers to get organic fertilizer.